Assessing Mobility Resilience and Vulnerability in the Context of Challenging Transportation Fare Policies: A Case Study of Rio de Janeiro - Santos, Tálita; Cardoso, Marcus; Silva, Marcelino Aurelio Vieira da; Fernandes, Vicente Aprigliano (Revista Brasileira de Gestão Urbana, 2024)
Resilience of urban mobility is an emerging topic, with most studies focusing on natural disasters or technical disturbances. However, there is a gap in understanding the resilience and vulnerability of urban mobility in the face of economic threats and inadequate transport policies, particularly in developing countries such as Brazil, characterized by social inequality and urban segregation. This study sheds light on the issue of urban inequalities and segregation, aiming to identify the most vulnerable and resilient areas of Rio de Janeiro in the event of an economic crisis. We assessed the resilience and vulnerability of the public transport system using commonly used accessibility indicators, applying fuzzy logic to data from 160 districts. We considered a scenario without the fare subsidy program. The results indicate that districts with better access to high-capacity transport systems and job opportunities exhibit higher levels of resilience and lower vulnerability. However, the study also uncovers socio-spatial inequalities, with resilience values tending to be higher in coastal areas and central business districts, exacerbating disparities. It is evident that addressing urban inequalities and segregation requires not only improving travel times and transportation systems but also considering the economic impact on vulnerable populations and promoting decentralized employment opportunities.